2015
DOI: 10.1101/gad.258863.115
|View full text |Cite
|
Sign up to set email alerts
|

A conserved intronic U1 snRNP-binding sequence promotestrans-splicing inDrosophila

Abstract: Unlike typical cis-splicing, trans-splicing joins exons from two separate transcripts to produce chimeric mRNA and has been detected in most eukaryotes. Trans-splicing in trypanosomes and nematodes has been characterized as a spliced leader RNA-facilitated reaction; in contrast, its mechanism in higher eukaryotes remains unclear. Here we investigate mod(mdg4), a classic trans-spliced gene in Drosophila, and report that two critical RNA sequences in the middle of the last 5 ′ intron, TSA and TSB, promote trans-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 56 publications
1
34
0
Order By: Relevance
“…Scientists are constantly looking for new fly research methods, which has undoubtedly accelerated the development of this model organism as well as other Drosophila species. Several studies have reported the use of genome editing techniques to introduce mutations in Drosophila cell lines (Böttcher et al, 2014 ; Gao et al, 2015 ; Lin et al, 2015 ; Mabashi-Asazuma et al, 2015 ; Kunzelmann et al, 2016 ), and a GFP-expressing cell line and comprehensive workflow were established for analyzing functional Drosophila genes. Thus, research at the cellular level will facilitate the optimization of the gene editing system and the establishment of a simple and convenient platform (Kunzelmann et al, 2016 ).…”
Section: Application Of Crispr/cas9 In Arthropodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientists are constantly looking for new fly research methods, which has undoubtedly accelerated the development of this model organism as well as other Drosophila species. Several studies have reported the use of genome editing techniques to introduce mutations in Drosophila cell lines (Böttcher et al, 2014 ; Gao et al, 2015 ; Lin et al, 2015 ; Mabashi-Asazuma et al, 2015 ; Kunzelmann et al, 2016 ), and a GFP-expressing cell line and comprehensive workflow were established for analyzing functional Drosophila genes. Thus, research at the cellular level will facilitate the optimization of the gene editing system and the establishment of a simple and convenient platform (Kunzelmann et al, 2016 ).…”
Section: Application Of Crispr/cas9 In Arthropodsmentioning
confidence: 99%
“…To improve the efficiency of genome editing, researchers found two smaller Cas9s (St1Cas9 and SaCas9) derived from S. thermophilus and Staphylococcus aureus , respectively, which are homologous to SpCas9. In addition, SpCas9 can recognize a transformed PAM site, such as NGCG, which significantly reduces the off-target effect (Gao et al, 2015 ; Kleinstiver et al, 2015 ).…”
Section: Sgrna Design and Off-target Effectsmentioning
confidence: 99%
“…The second example is lola , a gene that encodes at least 20 protein isoforms, one of which shows evidence of being trans -spliced ( Horiuchi et al 2003 ). In recent work, Gao et al (2015) have begun to elucidate the molecular mechanisms of trans -splicing in the mod(mdg4) and lola systems.…”
Section: Resultsmentioning
confidence: 99%
“…The bases of the introns of the two separate pre-mRNAs will pair with each other, bringing the two molecules together and thus promoting trans-splicing (Wally et al, 2012). However, a recent study in Drosophila showed that two intronic RNA sequence motifs are critical and perhaps sufficient to initiate trans-splicing in the mod gene (Gao et al, 2015). In both models, the nucleotide sequences of pre-mRNAs effect the conformation of the RNA-spliceosome complex and then influence splicing, which is essentially the same as cis-splicing.…”
Section: Discussionmentioning
confidence: 99%